Decrease in proven ventriculitis by reducing the frequency of cerebrospinal fluid sampling from extraventricular drains - Williams, T.; Leslie, Gavin; Dobb, G.; Roberts, B.; Van Heerden, P. (Amer Assoco Neurological Surgeons, 2011)
Ventriculitis associated with extraventricular drains (EVD) increases rates of morbidity and mortality as well as costs. Surveillance samples of CSF are taken routinely from EVD, but there is no consensus on the optimum frequency of sampling. The goal of this study was to assess whether the incidence of ventriculitis changed when CSF sampling frequency was reduced once every 3 days. Methods:After receiving institutional ethics committee approval for their project, the authors compared a prospective sample of EVD-treated patients (admitted 2008–2009) and a historical comparison group (admitted 2005–2007) at two tertiary hospital ICUs. A broad definition of ventriculitis included suspected ventriculitis (that is, treated with antibiotics for ventriculitis) and proven ventriculitis (positive CSF culture). Adult ICU patients with no preexisting neurological infection were enrolled in the study. After staff was provided with an education package, sampling of CSF was changed from daily to once every 3 days. All other management of the EVD remained unchanged. More frequent sampling was permitted if clinically indicated during the third daily sampling phase. Results: Two hundred seven patients were recruited during the daily sampling phase and 176 patients when sampling was reduced to once every 3 days.The Acute Physiology and Chronic Health Evaluation (APACHE) II score was lower for the daily sampling group than for the every-3rd-day group (18.6 vs 20.3, respectively; p < 0.01), but there was no difference in mean age (47 and 45 years, respectively; p = 0.14), male or female sex (61% and 59%, respectively; p = 0.68), or median EVD duration in the ICU (4.9 and 5.8 days, respectively; p = 0.14). Most patients were admitted with subarachnoid hemorrhage (42% in the daily group and 33% in the every-3rd-day group) or traumatic head injuries (29% and 36%, respectively). The incidence of ventriculitis decreased from 17% to 11% overall and for proven ventriculitis from 10% to 3% once sampling frequency was reduced. Sampling of CSF once every 3 days was independently associated with ventriculitis (OR 0.44, 95% CI 0.22–0.88, p = 0.02). Conclusions: Reducing the frequency of CSF sampling to once every 3 days was associated with a significant decrease in the incidence of ventriculitis. The authors suggest that CSF sampling should therefore be performed once every 3 days in the absence of clinical indicators of ventriculitis. Reducing frequency of CSF sampling from EVDs decreased proven ventriculitis.